Metafora Konseptual Bertema Rihlah (Jalan-Jalan) pada Majalah Gontor: Analisis Semantik Kognitif - Trian Ramadhan Nuryadin; Tajudin Nur (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2021)
This research is a cognitive semantic analysis and uses descriptive qualitative methods. The problems discussed in this study are the types of conceptual metaphors, namely (1) structural metaphors, (2) orientational metaphors, (3) metaphors. The theory used is the conceptual metaphor from Lakoff & Johnson (2003) as the main theory and the image scheme from Cruse & Croft (2004) theory. The data is taken from the Gontor magazine with the theme of